2005
DOI: 10.1177/0363546504267348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclic Loading on New Polyblend Suture Coupled with Different Anchors

Abstract: Use of the FiberWire suture might change the mode of failure of the suture-anchor complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 9 publications
0
48
0
1
Order By: Relevance
“…2 Fiberwire (Arthrex, Naples, FL, USA). These studies [1,19,20,53,55] unanimously agree that UHMWPE sutures have an Fig. 4 The arthroscopic rotator cuff repair.…”
Section: Suture Filament and Materialsmentioning
confidence: 84%
See 1 more Smart Citation
“…2 Fiberwire (Arthrex, Naples, FL, USA). These studies [1,19,20,53,55] unanimously agree that UHMWPE sutures have an Fig. 4 The arthroscopic rotator cuff repair.…”
Section: Suture Filament and Materialsmentioning
confidence: 84%
“…Recommendations are for best biomechanical construct, not necessarily best clinical outcome. Data pooled from multiple sources [1,19,20,53,55,81,82] Knee Surg Sports Traumatol Arthrosc (2009) …”
Section: Suture Filament and Materialsmentioning
confidence: 99%
“…Other cyclic or time-dependent studies have been performed to gain insight over monotonic pullout tests, [11][12][13][14][15][16][17] with many focused on pullout strength after a limited number of cyclic loads or on tendon gap formation. Several authors have created unique experiments to assess long-term performance.…”
mentioning
confidence: 99%
“…Consequently, there were three implantation sites: an anterior, a medial and a posterior site. The implantation site of every anchor type was regularly alternated in order to minimize the influence of possible variations in bone quality at the various positions (De Carli et al, 2005;Schneeberger et al, 2002). The suture anchors were inserted according to the manufacturers' instructions at a 451 angle to the diaphysis of the humerus (Burkhart, 1995).…”
Section: Placing the Suture Anchorsmentioning
confidence: 99%
“…There are many different testing protocols described in the literature. Suture anchors have been tested in bovine Coons et al, 2006;Koganti et al, 2006;Lee et al, 2005;Petit et al, 2003); ovine (Cummins et al, 2005;Klinger et al, 2007); porcine (Barber et al, 1996) and human (De Carli et al, 2005;Pietschmann et al, 2009) bone. Petit et al (2003) stated as reason for using bovine shoulder that the average bone mineral density of immature bovine bone is similar to that of young human bone, citing the work of Gibson and Ashby showed that the Young's moduli plotted against bone density of bovine and human cancellous bone of the femur have an almost identical distribution.…”
Section: Introductionmentioning
confidence: 99%